Human Resource Accounting and Financial Performance: Evidence from Indonesia’s Health Sector (2018–2023) - Rahmadhani, Novia; Sundari, Siti (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to examine the effect of Human Resource Accounting (HRA), proxied by employee training costs, salary costs, and pension costs, on financial performance, proxied by Return on Assets (ROA), in healthcare companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. Methodology: A quantitative approach with purposive sampling resulted in a final sample of 8 companies. Data were obtained through secondary documentation and analyzed using panel data regression with EViews 13. Results: The results show that employee salary costs have a significant positive effect on ROA (p < 0.05), while training and pension costs do not significantly impact financial performance (p > 0.05). Findings: The result underlines the strategic importance of competitive compensation, whereas the impact of training and pensions may be hindered by inconsistent implementation. Novelty: he study contributes new insights by applying panel data regression in the underexplored Indonesian healthcare sector and incorporating three HR cost indicators over a six-year period. Originality: This research uniquely focuses on post-pandemic financial performance in relation to HR cost efficiency in the healthcare sector. It also integrates Resource-Based Theory to interpret the strategic role of human capital in enhancing firm performance. Conclusion: Employee salary expenses significantly contribute to ROA, suggesting the importance of competitive compensation in improving financial outcomes. However, training and pension costs lack a direct and significant impact, implying that their effectiveness may depend on better alignment with corporate strategy and performance measurement systems. Future studies are encouraged to explore broader sectors and incorporate variables like HR accounting disclosure and wage dynamics. Type of Paper: Research Article.